Narrative sign restrictions for SVARs - Juan Antolín-Díaz; Juan Francisco Rubio-Ramírez (Federal Reserve Bank of Atlanta, 2016)
We identify structural vector autoregressions using narrative sign restrictions. Narrative sign restrictions constrain the structural shocks and the historical decomposition around key historical events, ensuring that they agree with the established narrative account of these episodes. Using models of the oil market and monetary policy, we show that narrative sign restrictions are highly informative. We highlight that adding a single narrative sign restriction dramatically sharpens and even changes the inference of SVARs originally identified via traditional sign restrictions. Our approach combines the appeal of narrative methods with the popularized usage of traditional sign restrictions.
Keywords: C32; E52; Q35; 330; narrative information; SVARs; Bayesian approach; sign restrictions; oil market; monetary policy